Conhecimento@sociedade.com.br/ambientesmidiaticos na supervia cibernética do tratamento informacional dos blogs brasileiros - Silva, Edileusa Regina Pena da (2010)
First of all, this Thesis follows a well-defined direction: to explain some structures, organizations and gears of the modern on line Social Communication, while addressing the components of love and affection that should never be absent from such processes, as essential requirements for the cognitive-evolutionary process of humans, especially in a postmodern society also emotionally affected by Information Technology. As result of the analysis of Brazilian blogosphere, it was revealed that the affective connections between people not only allows the exchange of information, knowledge, and experience, but above all emotions, affections, daily concerns, and a difuse human feeling beyond the barriers of space, time and format. Guided by the pillars of sociability and connective affection, our work starts from the premise that knowledge, combined with affection, can generate new visions of the world. It will also contribute to open minds and reformate thoughts, making us learn how to learn and interact with the New Communication and Information Technologies (NCIT's), always taking into account a real possibility of formation of subjects and proactive, inter-active participants on their own personal development, with priority issues that affect their community, their region, their nation. Thus, after analyzing the contents of six blogs in Brazilian blogosphere, we concluded, among other things, that man is capable of improving cognitive-intellectual abilities in favor of human, emotional, and educational growth. For reach these goals, however, we must find the means and the right conditions, in addition to learning how to share all this in a way humanly beneficial to all. One of the resolutions of one of the great enigmas of the Information Society by itself difficult to conceptualize adequately, even from its own denomination, which for some is post-modernity, and for other ones hypermodernity we might learn again to live together in social groups, developing feelings of connection with other people, a connection long ago lost in individualism (that now seems never to have existed!). This is, of course, the biggest challenge: (re)build the knowledge, and the wisdom, based on the taste for affection and brotherly love, in the midst of multiple social networks